Internalizing Islamic Education Values in Raising Environmental Awareness Character: a Case Study at Madrasah Tsanawiyah Negeri 2 Malang - Moch. Ainur Rofiq (Journal of Islamic Education Research, 2022)
Adiwiyata is one way to instill environmental awareness in the school community. MTs Negeri 2 Malang, as one of the participating schools in the Adiwiyata program, integrates the Adiwiyata program with subjects including religious subjects to internalize Islamic Education or PAI values ??so that students care about the environment. This study aims to determine the process of internalizing PAI values ??in raising environmental awareness character and their implications. This research uses a qualitative method with the type of case study research. The analysis used is descriptive. This study indicates that the PAI values internalized by students to foster environmental awareness characters are divided into three; aqidah, sharia, and akhlaq values. Internalizing these values ??goes through 3 stages; the value transformation, which focuses on cognitive abilities; the value transaction, which is a process of self-accustoming; and the transinternalization stage, where students are getting used to practicing the values ??that have been taught. From the internalization of values, there are changes in students' attitudes and behavior towards the environment.